Physicochemical characterization and thermodynamic studies of nanoemulsion-based transdermal delivery system for fullerene - Cheng, Loong Ngan; Basri, Mahiran; Tripathy, Minakaten; Abedi Karjiban, Roghayeh; Abd. Malek, Emilia (Hindawi Publishing Corporation, 2014)
Fullerene nanoemulsions were formulated in palm kernel oil esters stabilized by low amount of mixed nonionic surfactants. Pseudoternary phase diagrams were established in the colloidal system of PKOEs/Tween 80 : Span 80/water incorporated with fullerene as antioxidant. Preformulation was subjected to combination of high and low energy emulsification methods and the physicochemical characteristics of fullerene nanoemulsions were analyzed using electroacoustic spectrometer. Oil-in-water (O/W) nanoemulsions with particle sizes in the range of 70–160 nm were formed. The rheological characteristics of colloidal systems exhibited shear thinning behavior which fitted well into the power law model. The effect of xanthan gum (0.2–1.0%, w/w) and beeswax (1–3%, w/w) in the estimation of thermodynamics was further studied. From the energetic parameters calculated for the viscous flow, a moderate energy barrier for transport process was observed. Thermodynamic study showed that the enthalpy was positive in all xanthan gum and beeswax concentrations indicating that the formation of nanoemulsions could be endothermic in nature. Fullerene nanoemulsions with 0.6% or higher xanthan gum content were found to be stable against creaming and flocculation when exposed to extreme environmental conditions.